Standards of care, skill, diligence, and the business judgment rule in view of South Africa's Companies Act 71 of 2008: future implications for corporate governance - Mupangavanhu, Brighton Murisa (Department of Commercial Law, 2017)
Decision-making is the most critical role that company directors have to play in the life of a company that they are appointed to manage. South African law (in s66 of the Companies Act 71 of 2008, the Act) has now followed the global trend of recognising that directors have original authority/mandate to manage or direct company affairs or business. A director is accorded (by law) powers to exercise to enable him or her to fulfil the functions of that office. Decision-making, which is not an easy task, is critical to enterprise efficiency and advancement of the national economy. Directors have to make business decisions, at times under imperfect circumstances and while confronting tensions inherent in the corporate form. Not least of these tensions is the pressure to balance the profit maximisation drive from shareholders and accountability for how the directors exercise the powers at their disposal. Despite pressures involved in decision-making, the law requires that directors should exercise their powers in the best interests of the corporation. Thus the Act has attempted to put mechanisms in place to ensure that directors' freedom to manage corporations has to be necessarily constrained and balanced by the need for them to be accountable. The thesis focuses on the duty of care, skill and diligence on one hand (standard of conduct), and the business judgment rule (BJR- standard of review) on the other. These are two mechanisms put in place by the Act to ensure a balance between directors' freedom to manage and accountability. The thesis seeks to answer the key question whether the Act has made standards of care, skill and diligence clearer, more accessible and enforceable than before in light of the Act's adoption of BJR. The thesis analyses the duty of care, skill under s76(3)(c) and BJR under s76(4) in light of the context of law reform (that is the purposes of law reform) and international experiences. In this thesis, an appraisal of the positives brought about by the codification of the duty of care and the adoption of BJR into statute for the first time in SA is given. It is argued that while some purposes of law reform have been achieved, the Act has not achieved the purpose of clarity of standards. For example, the analysis reveals unfortunate omissions and worrying ambiguities in the formulation of standards of care, skill and diligence in s76(3)(c). While giving in-depth analysis of the scope and policy rationale of BJR under the Act, the thesis further notes that the characterisation of BJR in s76(4)(a) as a standard of conduct as opposed to standard of review is problematic. It has also been argued that the BJR is not properly aligned to international standards. Clear amendments to the Act have been suggested to improve clarity of standards and the law in s76(3)(c) and s76(4)(a).